The New Frontiers of Medical Malpractice: Legal Challenges in the Age of Artificial Intelligence and Telemedicine - Rosnalisa Zein; Iwan Kusnawirawan; Hernayati; Richard Mottershead; Muhammad Arsyad Subu; Imam Waluyo (Legalis : Journal of Law Review, 2024)
The healthcare landscape has transformed significantly in recent decades, propelled by technological advancements and evolving treatment methodologies. This evolution has improved patient care and introduced complexities in medical malpractice. This research aimed to explore the evolving landscape of medical malpractice in light of technological advancements such as artificial intelligence (AI) and telemedicine. Specifically, the study aims to analyze the gap between traditional legal standards of medical malpractice and the practical realities healthcare providers face in a rapidly changing environment. The gap is most evident when applying static legal definitions to an ever-changing healthcare environment.  This study employs a qualitative research method using a systematic literature review (SLR) to analyze the relationship between legal frameworks and technological developments influencing medical malpractice claims over the past five years (2018-2023).  This study found a pressing need for legal reforms to accommodate emerging technologies such as telemedicine and artificial intelligence (AI), which challenge conventional definitions of liability and standards of care. The study emphasizes the importance of adapting legal frameworks to ensure patient safety while protecting healthcare providers from undue liability. This study highlights medical malpractice law's dynamic and evolving nature in response to technological advancements and changing healthcare practices. Staying informed about these evolving legal standards is essential for healthcare providers' risk management and compliance. Policymakers must prioritize the development of supportive legal frameworks that protect patient rights while providing healthcare providers with the clarity needed to navigate this complex landscape effectively.